Analysis of a New Dissipation System for a Solar Cooling Installation. (8th December 2010) - Bailo, Carlos Monné; Garcés, Sergio Alonso; Arizón, Fernando Palacín
Abstract : This paper describes a solar absorption cooling installation located at the University of Zaragoza (Spain). The installation is based on the performance of an absorption chiller. The solar cooling system consists of 37, 5 m 2 of flat plate collector, a 4.5 kW, single-effect LiBr-H2 O absorption chiller, and a dry cooling tower. The installation provides cooling to a gymnasium belonging to the sports center of the university. To carry out the installation analysis, the system was continuously monitored. In 2007, 2008 and 2009, several studies have been performed in order to analyze the full system operation. The measured data showed the strong influence of the cooling water temperature and the generator driving temperature on the COP. Due to the experimental evidence of the influence of the cooling water temperature, a new heat rejection system based on a geothermal heat sink has been installed and studied.